Оптимізація зв’язності елементів в задачах автоматизованого проектування систем - Становський, Олександр Леонідович; Швець, Павло Степанович; Торопенко, Алла Володимирівна; Бондаренко, Віктор Володимирович; Становський, Андрій Олександрович; Абу шена, Осама Мохаммед Алі; Красножон, Олександр Миколайович (НТУ "ХПІ", 2015)
Показано, що оптимізація складних систем в САПР повинна враховувати в якості обмежень об’єктивно існуючий зв'язок в межах деякої області оптимізуючих аргументів між окремими елементами цих систем. Розглянуто проблему «зворотної» оптимізації, коли цільовими функціями є параметри області зв’язності. Теоретично доведені і практично підтверджені можливості зниження часу проектування та якості продукції електротехнічного виробництва за рахунок використання САПР, яка забезпечує ефективну оптимізацію параметрів слабозв’язаних підсистем об'єкта проектування з цільовою функцією у вигляді області зв'язності.

It is shown that the optimization of complex systems in the CAD should be taken into account as restrictions objectively existing relationship within a certain area of optimizing the arguments between the individual elements of these systems. The problems of "reverse" optimization where the target function parameters are the area of connectivity, which in many cases provides more efficient solutions in computer-aided design, are considered. It is theoretically proved and practically, by computer simulation and testing, confirmed the possibility of reducing the design time and product quality of electrical production through the use of CAD, which provides an effective optimization of parameters of loosely coupled subsystems of the design object with the objective function in the form of connectivity area. In SME STC "Techservice" (Odessa) it is conducted test of developed CAD «EVOSOFT». As the object of computer-aided design it is used transformer of the TM 25/10 / 0.4 model. As a result, the test found that the use of CAD «EVOSOFT» for electrical equipment is possible to reduce the weight of the transformer by 15 % while maintaining its consumer properties.
Connectivity optimization of the elements in the tasks of computer-aided system design
Keywords: оптимізація складних систем; параметри області зв’язності; зворотна оптимізація; САПР; complex systems; parameters of connectivity area; reverse optimization; CAD